Brand Revitalization for Pediatric Analgesic Product of PT TPI - Naim, Saekhun; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2012)
Currently, TMP brand is perceived on maturity to declining stage. Market share tends to shrinking, while the brand apparently starts losing its differentiation and relevance in the market. This journal is aimed to formulate a comprehensive analysis and to provide recommended action to conduct brand revitalization for TMP brand. The framework to conduct brand revitalization is started with brand life cycle analysis to define the stage of TMP in life cycle. Different stage demands for different strategic approach. Afterward, brand revitalization scorecard is deployed to ensure that TMP meets criteria as the right candidate for successful revitalization. Finally, the implementation of brand revitalization strategy is conducted using coherent concept of â€œPlan to Winâ€ modl. Keywords: Brand, Brand Life Cycle, Brand Revitalization Scorecard, Brand Revitalization